China in Zimbabwe: exploring the political and economic impacts of Chinese engagement in the Zimbabwean crises - Mvutungayi, Trust (My University, 2010)
ABSTRACT Between the years 2000-2009, Zimbabwe experienced the worst socio-economic and political challenges in its post- independence history. The period saw a spiral downfall of the economy in the midst of an increasingly unstable political landscape. As a result of the deteriorating economic environment and a worsening human rights record, Zimbabwe’s traditional aid donors and trading partners from the West began to disengage from the country, withdrawing their commercial and political support. In the midst of Western isolation and sanctions, China increased its stakes in Zimbabwe. China does not interfere in her partners’ domestic affairs hence she snubbed Western calls to put pressure on the Zimbabwean government for political and economic reforms. Thus, China offered both economic and political support in various forms to the Mugabe administration. China provided Zimbabwe with several trading arrangements, aid, loans, investments and as well as diplomatic support in the United Nations Security Council during the crisis period. The study explains the post-2000 nature of China’s increased engagement with Zimbabwe and explores the economic and political effects resulting from this close interaction. The study revealed that China’s support was important to bail out the Zimbabwean government against Western sanctions despite failing short of preventing the deterioration of the country’s political and economic situation.